Evaluation of research methodology in construction, productivity research - Vornichesku , O.; Shatrova , I. (Ways to Improve Construction Efficiency, 2023)
The article is aimed at considering the content of a large number of published works in the field of construction research and construction productivity, and at deriving an optimal model of construction research methodology based on the works examined. A particularly important issue is also the introduction of modern thinking with a discussion of the consequences for modern researchers. Articles published in both construction journals and broader management scientific journals were analyzed. Three broad classifications were used to summarize the methodologies adopted in the documents: qualitative, quantitative and mixed research methods. The research taxonomy also identified three main areas based on the research focus of each study: archival research, empirical research, and modeling proposals. In terms of the methodological structure followed, three main categories were recognized: experimental frameworks, data collection methods, and modeling proposals. Based on the results of the assessment, a methodological base was developed and its implementation in a real research project was illustrated. The main conclusion is that the choice of research methodology in published journal articles was an intuitive decision, mainly related to the ontological and epistemological position of the researcher. However, it is also possible to offer general guidance on the choice of the most appropriate methodology regarding the objectives and objectives of the study. Particular attention is paid to research related to the construction productivity CP. The CP field is an expedient area of study, since the complex and multifaceted nature of the subject led to the implementation of several methodological approaches. Thus, this study considers different points of view to measure or estimate construction performance.